WEB ARCHIVING AS CULTURE: TUMBLR AND THE CULTURAL CONSTRUCTION OF THE ARCHIVED WEB - Ogden, Jessica (AoIR Selected Papers of Internet Research, 2020)
Web archives - broadly conceived as any attempt to capture and preserve the Web for future use - are evermore central to discussions of digital access in the public sphere, as they provide tools for accessing parts of the Web that have been subject to neglect, removal or state and platform-based forms of content moderation and censorship. In this paper I discuss the cultural significance of web archiving through the example of Tumblr’s 2018 efforts to remove so-called ‘Not Safe for Work’ (NSFW) posts from the platform. The paper examines the archiving of Tumblr NSFW by Archive Team, a self-described ‘loose collective of rogue archivists, programmers, writers and loudmouths dedicated to saving our digital heritage’. Findings are presented through the concept of culture which provides a dual lens through which to understand web archiving practices as contingent upon the cultural worlds which they create and operate within. Here, web archiving as culture reveals the ways that practices shape (and are shaped by) online community membership, the nature of how and why the Web is archived and the reflexive significance participants place on their own web archival activities. The paper contributes to broader discussions of online community formation and raises further questions about the ethics and role of power in the production of web archives, as well as their positioning as historical representations of online cultures.